Review paperMental health problems in rheumatic diseases - Krzemińska-Dąbrowska, Izabela; Sudoł, Katarzyna; Moskalewicz, Bożena (Reumatologia/Rheumatology, 2007)
Rheumatic diseases are chronic disorders that may induce mental health problems at every stage of disease. Early diagnosis and effective psychological and psychiatric support are likely to improve the health status of patients and reduce the social costs of rheumatic diseases.